2013
DOI: 10.1002/jib.80
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic release of odourant polyfunctional thiols from cysteine conjugates in hop

Abstract: Polyfunctional thiols are contributors to the hop varietal aroma of beer. Besides free thiols, a cysteine-S-conjugate has recently been shown to be an additional component of the thiol potential of hop. Such cysteine adducts investigated here in four hop cultivars and in different hop forms. Hop hydroalcoholic extracts were purified on a cation exchanger and subjected to apotryptophanase β-lyase activity. The Cascade hop variety exhibited the highest bound 3-sulphanylhexan-1-ol (grapefruit-like) potential, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 37 publications
0
46
0
1
Order By: Relevance
“…These two compounds were later identified in fresh lager beers, and in Cascade, Nelson Sauvin and Super Alpha Tomahawk hop cultivars. In addition, a S ‐cysteinylated precursor of 3MH in hops able to release the 3MH under enzymatic mechanism was recently identified. Considering these aspects and by analogy with the enology field, we analysed ten hop varieties to demonstrate (i) the occurrence of both S ‐cysteinylated and S ‐glutathionylated conjugates of 3MH and 4MMP and (ii) to quantify them to have an approximation of their concentration ranges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two compounds were later identified in fresh lager beers, and in Cascade, Nelson Sauvin and Super Alpha Tomahawk hop cultivars. In addition, a S ‐cysteinylated precursor of 3MH in hops able to release the 3MH under enzymatic mechanism was recently identified. Considering these aspects and by analogy with the enology field, we analysed ten hop varieties to demonstrate (i) the occurrence of both S ‐cysteinylated and S ‐glutathionylated conjugates of 3MH and 4MMP and (ii) to quantify them to have an approximation of their concentration ranges.…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis point of view, first quantification results based on an indirect method (enzymatic cleavage of precursors and analysis of the released thiols) revealed that Cys3MH might be present until 1641 ppb as 3MH equivalent in Cascade . In addition, the same authors hypothesized the occurrence of 4MMP precursors in hops since they observed the release of 4MMP (up to 600 ppb equivalent of 4MMP in Nelson Sauvin variety) under their analytical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The previously synthesised ( 17, 20, 21 ) cysteinylated and glutathionylated precursors of 3SPol, 3SHol, and 3S4MPol were used for identification and quantitation. The two complementary columns ‐ strategy described by ( 17 ) ‐ was applied to identify and quantify these molecules in hop samples.…”
Section: Methodsmentioning
confidence: 99%
“…To establish the Cys‐3SHol/Cys‐3S4MPol ratio from the Cys‐3SHol+Cys‐3S4MPol amount obtained by HPLC‐MRM, an enzymatic treatment ( 20 ) was applied to hop precursors extracts. After dissolution in 2 mL of potassium phosphate buffered solution (100 mM, pH 7.7) containing pyridoxal 5‐phosphate (0.1 mM) and ethylenediaminetetraacetic acid (1 mM), the extract was mixed with 0.5 mL of a solution containing the commercial apotryptophanase from Escherichia coli (75–150 units/mg) freshly prepared (1 mg in 0.5 mL of buffer).…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the release of thiols has been studied first with a commercially available tryptophanase enzyme with strong carbon-sulfur β-lyase (CS β-lyase) activity towards cysteine-S-conjugates. Indeed, tryptophanase treatment could release the polyfunctional thiol 3-sulfanylhexan-1-ol (a key compound in passion fruit and grapefruit aroma) from extracts of aroma and dual-purpose hops (Gros, Tran and Collin 2013; Cibaka et al. 2015).…”
Section: Biosynthesis and Occurrence Of Fruity And Floral Aroma Compomentioning
confidence: 99%